2018
DOI: 10.1002/jper.18-0190
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐146a negatively regulates the inflammatory response to Porphyromonas gingivalis in human periodontal ligament fibroblasts via TRAF6/p38 pathway

Abstract: Background Human periodontal ligament fibroblasts (HPDLFs) represent the first line of defense against pathogens in the periodontal tissue. Porphyromonas gingivialis (P. gingivalis) has been known to be most strongly associated with periodontitis. MicroRNA (miR)‐146a is involved in the inflammatory regulation of periodontitis. However, the regulatory mechanism of miR‐146a on in P. gingivalis‐induced inflammation response in HPDLFs was still unclear. The aim of this study was to investigate whether miR‐146a pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…It is reported that suppression of TRAF6 inhibited the phosphorylation of p38 to decrease the expression of proinflammatory cytokines induced by Porphyromonas gingivalis in hPDLCs. 34 A20-TRAF6 axis is critical in modulating NF-κB pathway stimulated by LPS. The silence of A20 restores the expression of TRAF6, which upregulates the activity of NF-κB under the stimulation of LPS.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that suppression of TRAF6 inhibited the phosphorylation of p38 to decrease the expression of proinflammatory cytokines induced by Porphyromonas gingivalis in hPDLCs. 34 A20-TRAF6 axis is critical in modulating NF-κB pathway stimulated by LPS. The silence of A20 restores the expression of TRAF6, which upregulates the activity of NF-κB under the stimulation of LPS.…”
Section: Discussionmentioning
confidence: 99%
“…TRAF6 is the downstream of multiple receptors with immunoregulatory function, which plays a key role in immune system (Walsh et al, 2015). Furthermore, increasing studies suggested that TRAF6 functioned as a pro‐inflammatory agent in multiple inflammatory diseases (Ma et al, 2019; Tang et al, 2019; Wu et al, 2019). TRAF6 promoted inflammatory response in many conditions by activating NF‐κB signaling (Cui et al, 2018; Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study demonstrate that miR 146a-5p was successfully overexpressed in BV2 cells by transfection of miR mimic and that overexpression of miR repressed LPS-induced inflammatory response in these cells. NF-κB and p38 MAPK are two downstream signaling pathways that are activated after upregulation of TRAF6 and IRAK1 molecules [19,41]. miR 146a-5p downregulated the expression of target genes, including TRAF6 and IRAK1, subsequently reducing activation of the NF-κB and p38 MAPK pathways and the release of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%